(untitled) (Journal of Education and Development, 2018)
The primary purpose of this study was to investigate the content validity of the Junior Middle School Entrance English Testing. To understand the extent to which the test is consistent with the National Curriculum Standards, the qualitative and quantitative methods were implemented in this study, through the comparative analysis of the whole article’s items, and combined with the characteristic of the communicative language task to seek out whether the test content is relevant to the test objective, and to what extent it is representative. The most important thing is to find out whether the test content is suitable for the test object and to what extent. The results showed that the Junior Middle School Entrance English Test to some extent matches the syllabus, meanwhile, there are still some issues to exist. Finally, some suggestions were put forward by the author.